Therapeutic lymphography for persistent chyle leak after pancreatic surgery - Klotz, Rosa; Kuner, Charlotte; Pan, Feng; Feißt, Manuel; Hinz, Ulf; Ramouz, Ali; Klauß, Miriam; Chang, De-Hua; Do, Thuy; Probst, Pascal; Sommer, Christof-Matthias; Kauczor, Hans-Ulrich; et al. (HPB, 2022)
Background - Chyle leak is a common complication following pancreatic surgery. After failure of conservative treatment, lymphography is one of the last therapeutic options. The objective of this study was to evaluate whether lymphography represents an effective treatment for severe chyle leak (International study Group on Pancreatic Surgery, grade C) after pancreatic surgery. - Methods - Patients with grade C chyle leak after pancreatic surgery who received transpedal or transnodal therapeutic lymphography between 2010 and 2020 were identified from a prospectively maintained database. Clinical success of the lymphography was evaluated according to percent decrease of drainage output after lymphography (>50% decrease = partial success; >85% decrease = complete success). - Results - Of the 48 patients undergoing lymphography, 23 had a clinically successful lymphography: 14 (29%) showed partial and 9 (19%) complete success. In 25 cases (52%) lymphography did not lead to a significant reduction of chyle leak. Successful lymphography was associated with earlier drain removal and hospital discharge [complete clinical success: 7.1 days (±4.1); partial clinical success: 12 days (±9.1), clinical failure: 19 days (±19) after lymphography; p = 0.006]. No serious adverse events were observed. - Conclusion - Therapeutic lymphography is a feasible, safe, and effective option for treating grade C chyle leak after pancreatic surgery.
First published: 7 October 2021
Gesehen am 18.08.2022